Subjective theories of prosocial behavior: Meanings, development and motivations of young volunteers in the face of a socionatural disaster - Alvarado Ardiles, Robert (2019)
Objective: the present work aims to learn about the subjective theories of the prosocial behavior of young volunteers during the response and recovery stages of a socionatural disaster. Method: a qualitative case design was used by selecting, through intentional sampling, 11 university students who volunteered in the face of the hydrometeorological disaster occurred in Atacama, Chile. Data was collected through semi-structured interviews and a discussion group, using the coding process in grounded theory as an analysis strategy. Results: we found that (i) volunteers understand prosocial behavior as a process of limited-temporality humanitarian aid which depends on empathy towards those affected; the perception of institutional (in)capacity; a subjective risk assessment; self-perceived abilities; and a sense of social responsibility in the face of a disaster; (ii) its development is linked to an early value training, which is maintained by the constant participation in this type of activities over time and the emotional support of significant third parties; and (iii) the types of motivation to show this helping behavior are extrinsic-social and intrinsic-personal. Conclusions: the importance of the training-educational process for strengthening prosocial behavior is supported, as well as the importance of formalizing the volunteer recruitment process in the face of these events.